Comprehensive tax reform : the Colombian experience - Shome, Parthasarathi (IMF WashingtonUS, 1995)
Analyzes particular areas of tax policy that have concerned the Colombian authorities during the 1990s. Looks at selected structural aspects and revenue potential of the VAT and the impact of income tax on investment and revenue and inflation adjustment potentials. Examines the customs tariff reform of 1992, including its revenue consequences and some alternative reform packages. Focuses on the direction of future reforms.